Fashion engagement and pro-environmental attitudes: drivers of sustainable fashion consumption in Indonesia - Ahmad Nuh; Muhammad Misbakul Munir; Muhibban Muhibban (Journal of Enterprise and Development (JED), 2023)
Purpose — The purpose of this research is to explore the relationship between fashion involvement, pro-environmental attitudes, and consumption of sustainable fashion in the Indonesian market.Method — The research was conducted in the Capital City of Jakarta and satellite cities, involving 236 respondents from three generational groups (Gen X, Gen Y, Gen Z). The study employed surveys to gather data on fashion involvement, pro-environmental attitudes, and sustainable fashion consumption.Result — The findings of the study indicate that both fashion engagement and pro-environmental attitudes have a significant and positive relationship with the consumption of sustainable fashion in the Indonesian market. The research also highlights the importance of social norms and attitudes in influencing sustainable fashion purchasing behavior.Contribution — This research provides valuable insights into the factors driving sustainable fashion consumption in Indonesia through the influence of fashion engagement and pro-environmental attitude variables on three different generational groups, namely gen X, gen Y, and gen Z in Indonesia.